Investigation of Endocytic Pathways for the Internalization of Exosome-Associated Oligomeric Alpha-Synuclein - Delenclos, Marion; Trendafilova, Teodora; Mahesh, Divya; Baine, Ann M.; Moussaud, Simon; Yan, Irene K.; Patel, Tushar; McLean, Pamela J. (Frontiers in Neuroscience, 2017)
Misfolding and aggregation of alpha-synuclein (αsyn) resulting in cytotoxicity is a hallmark of Parkinson’s disease (PD) and related synucleinopathies. The recent body of evidence indicates that αsyn can be released from neuronal cells by nonconventional exocytosis involving extracellular vesicles (EVs) such as exosomes. The transfer of αsyn between cells has been proposed to be an important mechanism of disease propagation in PD. To date, exosome trafficking mechanisms, including release and cell-cell transmission, have not been fully described. To gain insight into the mechanisms involved, exosomes were purified from conditioned media of stable cells secreting αsyn oligomers. A novel bimolecular protein complementation assay was used to detect exosomes containing αsyn oligomers. Recipient cells were treated with exosomes containing αsyn oligomers or “free” non-exosome-associated αsyn oligomers and internalization was monitored. We demonstrate that cell-derived exosome-associated αsyn oligomers can be efficiently internalized by recipient cells. Interestingly exosome-free αsyn oligomers isolated from conditioned medium were not internalized but remained bound to the extracellular surface. To investigate the endocytic pathway(s) required for the exosome uptake different pharmacological inhibitors of caveolin-dependent, clathrin-dependent, and macropinocytosis pathways were utilized. Surprisingly, none of these pathways appear to play a significant role in the internalization of exosome-associated αsyn oligomers. Finally, the role of heparin sulfate proteoglycans (HSPGs) in exosome-associated αsyn internalization was investigated using genetic approach. Despite previous studies showing HSPGs can modulate internalization of fibrillar αsyn, genetic manipulations did not attenuate internalization of exosome-associated αsyn oligomers in our hands, suggesting that exosome-associated αsyn is internalized via an alternative endocytic pathway(s) that has yet to be elucidated.